THE INFLUENCE OF TRAINING AND HUMAN RESOURCES DEVELOPMENT ON THE PERFORMANCE OF EMPLOYEES OF THE COMMUNICATIONS AND INFORMATICS OFFICE OF Tulang Bawang District - Yati, Indra; Ayu, Maristiana (University of Sang Bumi Ruwa Jurai, 2023)
The phenomenon that occurs at the Department of Communication and Informatics of Tulang Bawang Regency regarding employee training is the minimum number of trainings attended by employees. The phenomenon that occurs related to the development of human resources in the Department of Communication and Informatics in Tulang Bawang Regency is still not optimal. Seeing and paying attention to the problems of HR training and development as described above, it is suspected that this accumulation of problems also contributes to weak performance, this can be seen from the realization of the implementation of work targets that are not according to plan. The formulation of the problem in this study is whether the influence of training and development of human resources either partially or simultaneously on employee performance. The purpose of this study was to study the influence of training and human resource development on employee performance. The hypothesis in this study is that there is an influence of training and human resource development either partially or simultaneously on employee performance. The sample in this study amounted to 40 employees. Data collection techniques include observation, data collection and questionnaires. Methods of data analysis using a quantitative approach with the help of statistical tools SPSS version 21.0 includes the calculation of validity tests, reliability tests, simple and multiple linear regression tests, t tests, F tests and tests of the coefficient of determination. The results of hypothesis testing show that the training variable partially has a positive influence on performance with a contribution of 54.3%. Human resource development has a positive influence on performance with a contribution of 49.6%. Simultaneous hypothesis testing shows that training and human resource development variables together have a positive influence on employee performance variables with a contribution of 58.7%